2021
DOI: 10.1080/21691401.2021.1879104
|View full text |Cite
|
Sign up to set email alerts
|

PEG-interpenetrated genipin-crosslinked dual-sensitive hydrogel/nanostructured lipid carrier compound formulation for topical drug administration

Abstract: 2021) PEG-interpenetrated genipin-crosslinked dual-sensitive hydrogel/ nanostructured lipid carrier compound formulation for topical drug administration, Artificial Cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…As shown in Figure S1, the characteristic peak at 3290 cm –1 of spectrum [A] was due to the −NH stretching vibrations of the aromatic ring of clozapine, and the bands observed at 2773, 2800, 2934, and 2970 cm –1 corresponded to the aliphatic −CH stretching of clozapine. , The FTIR spectrum of oleic acid [B] showed peaks at 2853 and 2922 cm –1 , which were associated with symmetric and asymmetric −CH 2 stretching bands, respectively. The peak at 1708 cm –1 was due to the CO stretch of oleic acid. , The P407 spectrum [C] showed characteristic peaks at 2883 cm –1 (−CH stretching), 1467 cm –1 (−CH 2 bending), 1342 cm –1 (−OH bending), and 1100 cm –1 (C–O stretching). , The bands observed for the PS80 spectra [D] were 3503 cm –1 (−OH stretching), 2921 cm –1 (−CH 2 stretching), 2860 cm –1 (CH 3 stretching), 1735 cm –1 (CO stretching), and 1097 cm –1 (C–O–C stretching). , In the propylene glycol spectrum [E], the broad absorption band at 3308–3310 cm –1 was ascribed to −OH stretching, while 2970, 2930, and 2875 cm –1 were due to −CH stretching and 1040 cm –1 was due to C–O stretching vibrations . The CLZ-NESG spectra [F] showed a wide absorption band at 3688–3032 cm –1 (−OH stretching) due to the presence of PS80 and propylene glycol (at 10% w / w ) in the formulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S1, the characteristic peak at 3290 cm –1 of spectrum [A] was due to the −NH stretching vibrations of the aromatic ring of clozapine, and the bands observed at 2773, 2800, 2934, and 2970 cm –1 corresponded to the aliphatic −CH stretching of clozapine. , The FTIR spectrum of oleic acid [B] showed peaks at 2853 and 2922 cm –1 , which were associated with symmetric and asymmetric −CH 2 stretching bands, respectively. The peak at 1708 cm –1 was due to the CO stretch of oleic acid. , The P407 spectrum [C] showed characteristic peaks at 2883 cm –1 (−CH stretching), 1467 cm –1 (−CH 2 bending), 1342 cm –1 (−OH bending), and 1100 cm –1 (C–O stretching). , The bands observed for the PS80 spectra [D] were 3503 cm –1 (−OH stretching), 2921 cm –1 (−CH 2 stretching), 2860 cm –1 (CH 3 stretching), 1735 cm –1 (CO stretching), and 1097 cm –1 (C–O–C stretching). , In the propylene glycol spectrum [E], the broad absorption band at 3308–3310 cm –1 was ascribed to −OH stretching, while 2970, 2930, and 2875 cm –1 were due to −CH stretching and 1040 cm –1 was due to C–O stretching vibrations . The CLZ-NESG spectra [F] showed a wide absorption band at 3688–3032 cm –1 (−OH stretching) due to the presence of PS80 and propylene glycol (at 10% w / w ) in the formulation.…”
Section: Resultsmentioning
confidence: 99%
“…51,52 The P407 spectrum [C] showed characteristic peaks at 2883 cm −1 (−CH stretching), 1467 cm −1 (−CH 2 bending), 1342 cm −1 (−OH bending), and 1100 cm −1 (C−O stretching). 53,54 The bands observed for the PS80 spectra [D] were 3503 cm −1 (−OH stretching), 2921 cm −1 (−CH 2 stretching), 2860 cm −1 (CH 3 stretching), 1735 cm −1 (C�O stretching), and 1097 cm −1 (C−O−C stretching). 55,56 In the propylene glycol spectrum 4.5.…”
Section: Dsc and Tga Studiesmentioning
confidence: 99%
“…After loading the alpha-lipoic acid (ALA) nanostructured lipid carrier (ALA-NLC) with high efficiency, experiments showed that increasing PEG accelerated the drug release rate. 72 In another study, gold nanoparticles embedded in P407 showed excellent colloidal stability and slow and sustained drug release behavior. 73…”
Section: Temperature Sensitive Hydrogelsmentioning
confidence: 96%
“…However, alginate-based dressings have poor structural stability . Therefore, strategies like plasticization have been used to reduce intermolecular attractive forces between polymer chains and improve the structural stability of alginate-based aerogels. , Moreover, the transdermal delivery of ALA in a poly­(ethylene glycol)-plasticized aerogel is improved . Thus, alginate aerogels can be designed to control bleeding, exudate, and superficial infection and to deliver molecules.…”
Section: Introductionmentioning
confidence: 99%